New (Un)certainty in Will Self’s Dorian: An Imitation and Colm Tóibín’s "The Master" - Yebra, José M. (Estudios Ingleses de la Universidad Complutense, 2012)
This essay aims at exploring how the controversy between postmodernist uncertainty and new movements claiming for a new certainty determine the discourse of Will Self’s Dorian: An Imitation (2002) and Colm Tóibín’s The Master (2004). After revising how this controversy has its roots deep in the history of art discourses, the article draws on postpostmodernist theories such as Raoul Edelman’s performatism, Gilles Lipovetsky’s hypermodernism and Alan Kirby’s digimodernism. Although they help us understand texts at the turn of the millennium, they also prove eventually unsatisfactory in some cases. The analysis demonstrates that Self’s and Tóibín’s novels apparently aim at a new sense of certainty to represent homoerotic desire and its manifestations, as a roman à clef and a biofictional text respectively. However, certainty soon proves to be unfeasible as both novels turn to the precariousness and irony characteristic of postmodernism.